Motivasi Sumber Daya Manusia Dipengaruhi Oleh Kebutuhan - Affandy Agusman Aris (Journal on Education, 2024)
Humans will be moved when in need, a person's needs are motivated to do something so that what is needed is realized. Motivation is formed from the employee's attitude in facing work situations in the company (situation). Motivation is a condition or energy that moves employees who are directed or directed towards achieving the company's organizational goals. For this reason, companies need to create conducive conditions that make their employees feel comfortable, their needs are met, so that it is hoped that their motivation will be maintained to jointly achieve the Company's vision and mission. Unmet needs create tension that stimulates drives from within the individual to achieve the intended goal. This drive gives rise to a search behavior to find certain goals which, if achieved, will fulfill needs and lead to a reduction in tension. Each person is highly motivated to behave in a way that meets his or her needs and the key to a leader's success lies in the ability to motivate organizational members in an effort to fulfill and support these “high level” needs so that organizational goals can be achieved. leaders in motivating their members should Motivate members of the organization by motivating themselves. A good place to start learning about motivation is learning to start understanding your own motivation. If leaders are enthusiastic about their work, then it is much easier to motivate other members of the organization. The key to supporting the motivation of organizational members is understanding what motivates each of them. Everyone is motivated by different things. Whatever steps the leadership takes to support the motivation of its members, they must first find out what really motivates them. Leadership can discover this by asking members, listening to them and observing them. Recognizing that supporting work motivation is a process, not a task means that Organizations change over time, just like people. Indeed, it is a continuous process to maintain an environment where everyone can be self-motivated. If Leaders see member motivation as an ongoing process, then Leaders will be much more fulfilled and self-motivated.